Bringing Islamic Justice to Life: Criticizing the Mechanisms of Zakat, Alms, and Waqf in the Era of Globalization - Muhammad Solihin Sahal (Codeverse: Journal of Emerging Digital Realities, 2025)
This study examines the mechanisms of zakat, sadaqah, and waqf as key components of the Islamic economic system, focusing on their effectiveness in promoting social justice in the context of globalization. The research identifies several challenges in the management of these instruments, including issues related to infrastructure, transparency, public awareness, and regulatory frameworks. The study proposes integrating digital technologies to enhance the efficiency, accountability, and transparency of zakat and waqf management. Through qualitative research involving interviews and field observations, the study highlights the importance of multi-sector collaboration between public, private, and civil society institutions in optimizing these mechanisms. The findings suggest that the adoption of technology, better governance, and improved public education can significantly improve the effectiveness of zakat, sadaqah, and waqf, contributing to more equitable wealth distribution and sustainable socio-economic development.